Study on the Development of Avocado (Persea Americana) Stirred Yoghurt - Reddy, P. Madhusudhan; Marid, T. (International Journal of Economic Plants, 2022)
This study was aimed in the month and year on December, 2021 to develop avocado (Persea Americana) pulp incorporated stirred yoghurt and determine the sensorial properties. Fresh cow milk was procured from the Dairy farm. Cow milk was standardized up to 3% fat level and pasteurized at 85oC/30 min. Then the milk was cooled and starter cultures inoculate at 45oC (2% addition per kg milk) and incubate for about 4 hrs until acidity 0.7–0.8% lactic acid for the preparation of yoghurt. Fresh ripened avocado were purchased from local market. The ripen flesh was extracted, well blended until turn in to a smooth cream and pasteurized. The avocado pulp and yoghurt were blended properly. Avocado stirred yoghurt was prepared using different inclusion rates; 0%, 5%, 10% and 15% of avocado pulp, 18% sugar syrup of 50% concentration and compared with control. Sensory attributes such as Colour and Appearance, Body and Texture, Flavour and Overall acceptability were analyzed by using hedonic scale in all samples. All samples were evaluated by trained and untrained judges. 10% avocado pulp collusion rate was preferred significantly. The sensory scores of overall acceptability of control (0% avocado pulp), 5%, 10% and 15% avocado stirred yoghurt are 6.64, 6.72, 7.68 and 7.42 respectively. This study revealed that 10% inclusion of avocado pulp in stirred yoghurt make consumer preferred dairy product which can be improved in future studies.